Global Value Chains, Economic Upgrading, and Gender : Case Studies of the Horticulture, Tourism, and Call Center Industries - Staritz, Cornelia; Reis, José Guilherme (Washington, DC, 2014)
This document provides a gendered analysis of the horticulture, tourism, and call center global value chains (GVCs), based on a survey of the literature and case studies carried out in Honduras, Kenya, and the Arab Republic of Egypt. The studies focus on export sectors that have had high female employment and have been relatively underexplored from the angle of trade and gender research. The studies show that GVCs and their upgrading dynamics have important gender dimensions, and that integration and upgrading are influenced by, and have an impact on, gender relations. While the conditions and dynamics in the sectors in concern are very different, certain broad conclusions are drawn from the results of the studies. The first is that patterns of job segregation are observed in all case studies, with women being assigned to specific jobs, though the reasons for such segregation differ from sector to sector. The second conclusion is that women face gender-intensified constraints, though their extent and articulation may be quite different, depending on the value chain. The third is that constraints related to women's primary responsibility for reproductive work have been identified as important in all three studies. This social division of labor is deeply embedded in developed and developing countries, but poor infrastructure, particularly in rural areas, heightens this challenge for women in developing countries. This report also suggests appropriate interventions to improve the constraints faced by women.